PERILAKU PANGAN TERBUANG PADA KONSUMSI RUMAH TANGGA DAERAH DATARAN TINGGI DI KECAMATAN SIMPANG HULU KABUPATEN KETAPANG - Setiawan, Tobias Riyadi; maswadi, maswadi; Sauharyani, Anita (Lampung University, 2025)
Food waste is a serious global issue in countries, including in Indonesia. Various factors contribute to food waste at the household level, which is a primary sector in the food supply chain. According to the data from BAPPENAS and SIPSN, household food waste accounts for a significant portion of the total food waste in Indonesia, with household consumption reaching up to 19 million tons per year. This study aims to examine the food waste behavior of consumer households in highland areas, in Simpang Hulu District. The number of samples examined in this study consists of 63 respondents. The research employed a quantitative descriptive method. Based on the results concerning personal norms, awareness of consequences, and a sense of responsibility related to food waste behavior in highland households, it is concluded that food waste is considered undesirable. Housewives in highland areas demonstrate high awareness of impacts of food waste and are committed to manage food efficiently for the welfare of their families. Various age groups also show positive awareness of the importance of reducing food waste, and start to plan meals properly. Additionally, various income classes exhibit a positive understanding of the responsibility to reduce food waste, indicating that economic factors do not hinder acting responsibly towards the environment and food. Household food expenditure and the number of family members do not affect the awareness, regarding the shared responsibility in managing food and protecting the environment. Overall, food waste behavior in highland households is driven by high awareness and shared responsibility to minimize food waste and maintain environmental sustainability. Key words: Food Waste, Household, NAM